Association between blood ethylene oxide levels and periodontitis risk: a population-based study - Liu, Yixuan; Liu, Nuozhou; Xiong, Wei; Wang, Ruiyu (Frontiers in Public Health, 2024)
Background The etiopathogenesis of periodontitis is closely associated with environmental conditions. However, the relationship between ethylene oxide exposure and periodontitis risk remains unclear. Methods We selected qualified participants from National Health and Nutrition Examination Survey (NHANES) 2013–2014. Periodontitis was identified according to the criteria of the Community Periodontal Index (CPI), Centers for Disease Control and Prevention (CDC)/American Academy of Periodontology (AAP) definition. Ethylene oxide exposure was quantified by hemoglobin adducts of ethylene oxide (HbEO) levels. Log2-transformation was used to normalize HbEO levels. We designed three logistic regression models to explore potential relationship between HbEO and periodontitis. Restricted cubic spline (RCS) and subgroup analysis were also conducted with all covariates adjusted. We performed multivariable linear regression to appraise the association between the risk of periodontitis and different indicators of inflammation, including white blood cells, neutrophils, lymphocytes, and monocytes. Mediation analysis was subsequently performed to examine whether ethylene oxide exposure contributed to periodontitis development through systemic body inflammation. Results A total of 1,065 participants aged more than 30 were incorporated in this study. We identified that participants with higher HbEO levels showed increased risk of periodontitis after adjusting for all covariates (OR = 1.49, 95% CI: 1.14, 1.95, p = 0.0014). The results of subgroup analysis remained stable. The restricted cubic spline (RCS) curve also revealed a non-linear correlation between log2-transformed HbEO levels with the risk of periodontitis (p for nonlinear < 0.001). Mediation analysis indicated that HbEO level was significantly associated with four inflammatory mediators, with the mediated proportions of 14.44% (p < 0.001) for white blood cell, 9.62% (p < 0.001) for neutrophil, 6.17% (p = 0.006) for lymphocyte, and 6.72% (p < 0.001) for monocyte. Conclusion Participants with higher ethylene oxide exposure showed higher risk of periodontitis, which was partially mediated by systemic body inflammation. More well-designed longitudinal studies should be carried out to validate this relationship.